2016
DOI: 10.1111/deci.12253
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Revenue Sharing with Daily Deal Sites: A Competitive Analysis

Abstract: Promoting through daily deal sites has become popular in the past few years. Groupon is perhaps the best known provider of these promotions (also known as online discount vouchers) to customers. Daily deals differ from traditional coupons on three important dimensions: (i) They are not offered to consumers directly by firms but are offered through an intermediary, (ii) the promotional depth offered by these localized promotions tends to be higher, and (iii) consumers prepay for the discount vouchers, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…They provide evidence of the negative effect of refunds and design the best refund and revenue-sharing policy. Observing that daily trading websites such as Groupon have become popular, Bhardwaj and Sajeesh (2017) develop a multistage game model to study the profitability of a company's online discount voucher strategy. They show that the types of consumers in the market, relative bargaining power of the local companies, revenue-sharing agreement, and market characteristics (the degree of product substitutability and competitive intensity) are all important drivers of the profitability of daily deal promotions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They provide evidence of the negative effect of refunds and design the best refund and revenue-sharing policy. Observing that daily trading websites such as Groupon have become popular, Bhardwaj and Sajeesh (2017) develop a multistage game model to study the profitability of a company's online discount voucher strategy. They show that the types of consumers in the market, relative bargaining power of the local companies, revenue-sharing agreement, and market characteristics (the degree of product substitutability and competitive intensity) are all important drivers of the profitability of daily deal promotions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For more classic literature on competition, readers are referred to Fudenberg and Tirole (1991), Lippman and McCardle (1997), and Bhardwaj and Sajeesh (2017). However, most of the above papers overlook the effect of fixed capacity, which is an important factor that affects revenue in practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The di erence is that we focus on the market structure including the o ine and online consumer size and product cost, while they emphasize consumers' behavior in group buying, that is, the sensibility for the cost to look for people to join group buying together. Bhardwaj and Sajeesh (2017) [23] considered the bargaining power of sellers and the website, and found that when the two retailers compete with each other, the website prefers cooperating with one of them rather than both. Subramanian and Rao (2016) [24] used a traditional revenue sharing model to distribute the total groupbuying revenue.…”
Section: Literature Reviewmentioning
confidence: 99%